2016
DOI: 10.13052/jiems2446-1822.2016.007
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Level of Light Pollution and Its Impact on Astronomical Bodies Naked-Eye Visibility Range in Selected Areas in Malaysia Using Sky Quality Meter

Abstract: Light pollution is an anthropogenic by-product of modern civilization and heavy economical activity, sourced from artificial light. In addition of its detrimental impact on human and ecology, light pollution brightens the night sky, limiting the range of visible astronomical bodies detected by naked-eye. Since it is becoming a global concern for astronomers, the level of light pollution needs to be monitored to study its mark on the astronomical data. Using Sky Quality Meter in the period of 5 months, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…The trend exhibited similarities to previous findings in urban and suburban sites, peaked during daytime (2 p.m.), and decreased during nighttime, but the concentrations differed [14,16,17,35]. Faid et al [24] investigated the profile of the night sky in Malaysia. They found that population and location distance from a city are the significant variables of light pollution because Kuala Lumpur is five times brighter than Teluk Kemang, a suburban sky.…”
Section: Hourly Diurnal Variation In Urban and Suburban Areasupporting
confidence: 79%
See 1 more Smart Citation
“…The trend exhibited similarities to previous findings in urban and suburban sites, peaked during daytime (2 p.m.), and decreased during nighttime, but the concentrations differed [14,16,17,35]. Faid et al [24] investigated the profile of the night sky in Malaysia. They found that population and location distance from a city are the significant variables of light pollution because Kuala Lumpur is five times brighter than Teluk Kemang, a suburban sky.…”
Section: Hourly Diurnal Variation In Urban and Suburban Areasupporting
confidence: 79%
“…These sites were situated in the cities where the population density was higher than that of suburban sites, i.e., Muar (MR), Indera Mahkota (IM), and Tanjung Malim (TM). A city is considered a significant contributor to light pollution because of more artificial light sources, such as street lights, security lights, lights on vehicles, and lighted buildings and towers that vary to many degrees [1,24].…”
Section: Light Pollution In Urban and Sub-urban Areasmentioning
confidence: 99%
“…Light pollution is an alteration of the natural night sky through artificial lighting that causes the night sky to be brighter and deforms the natural brightness and colour of the night sky (Faid et al, 2019). As light pollution brightens the sky and distorts the supposed colour of the night sky, it hampers astronomical sightings such as stars, galaxies and the Milky Way (Faid et al, 2016). This is because astronomical objects require certain brightness and colour contrast thresholds against the night sky to be visible.…”
Section: Methodology Identification Of Astrotourism Sitementioning
confidence: 99%
“…Rapid development occurred in industrial activities such as manufacturing, factories, processing, shipping, and tourism (Othman & Latif, 2020). The urban area was facilitated with more artificial light sources; streetlights, security lights, lights on vehicles and lighted buildings that may contribute to light pollution that varies in many degrees (Faid et al, 2016).…”
Section: Urban and Sub-urban Locationmentioning
confidence: 99%